2012
DOI: 10.1208/s12248-012-9339-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Development of Nanoparticle-Based Therapeutics

Abstract: In recent years, nanotechnology has been increasingly applied to the area of drug development. Nanoparticle-based therapeutics can confer the ability to overcome biological barriers, effectively deliver hydrophobic drugs and biologics, and preferentially target sites of disease. However, despite these potential advantages, only a relatively small number of nanoparticle-based medicines have been approved for clinical use, with numerous challenges and hurdles at different stages of development. The complexity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
506
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 772 publications
(517 citation statements)
references
References 82 publications
(93 reference statements)
4
506
0
7
Order By: Relevance
“…Further increasing the amount of Tf from 1.0 to 1.5 mg and the Lf density increased from 10.7 to 13.0 μg/mg, the PS increased from 151.0 to 163.5 nm. Also, the conjugation efficiency dropped from 80.3% to 65.0% with an increase in Tf from 1.0 to 1.5 mg. For, intravenous administration, the preferable PS is below 200 nm, and hence considering the size and conjugation efficiency, 1.0 mg of Tf/Lf was considered as optimized amount (42). The conjugation of amino group of the Tf and Lf to the epoxy group was estimated and found to be 10.6 μg Tf/mg NPs and 11.1 Lf/mg NPs, which represents approximately 186 Tf molecules per NP and 185 Lf molecules per NP.…”
Section: Functionalization Of Ltg-npmentioning
confidence: 99%
“…Further increasing the amount of Tf from 1.0 to 1.5 mg and the Lf density increased from 10.7 to 13.0 μg/mg, the PS increased from 151.0 to 163.5 nm. Also, the conjugation efficiency dropped from 80.3% to 65.0% with an increase in Tf from 1.0 to 1.5 mg. For, intravenous administration, the preferable PS is below 200 nm, and hence considering the size and conjugation efficiency, 1.0 mg of Tf/Lf was considered as optimized amount (42). The conjugation of amino group of the Tf and Lf to the epoxy group was estimated and found to be 10.6 μg Tf/mg NPs and 11.1 Lf/mg NPs, which represents approximately 186 Tf molecules per NP and 185 Lf molecules per NP.…”
Section: Functionalization Of Ltg-npmentioning
confidence: 99%
“…However, curtailing vector-associated toxicity is technically challenging. Therefore, biomaterials that are biocompatible, bioresponsive, and biodegradable could be advantageous over synthetic vectors and continue to be actively developed (8,9). To investigate the tumor targeting and therapeutic efficacy of Affi HER2 Vacuole Dox in vivo, we used a HER2-overexpressing NIH3T6.7 cell-based mouse xenograft model (37).…”
Section: Resultsmentioning
confidence: 99%
“…Such nanomaterial-based drug delivery systems have shown improved therapeutic efficacy with lower unwanted adverse effects compared with conventional chemotherapy, at least in animal models (1)(2)(3)(4)(5). Despite the appreciable success of cancer nanomedicines in preclinical studies, only a few such agents have entered clinical trials, and fewer still have shown promising therapeutic outcomes and advanced to subsequent trial stages (6)(7)(8). Among factors likely to hamper the clinical feasibility of synthetic cancer-targeting nanomaterials are technical challenges involving their pilot scale, cost-effective production, and intrinsic cytotoxicity associated with these materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, experts from academia, industry and regulatory bodies suggest a stepwise similarity approach that includes appropriate clinical and/or nonclinical studies that evaluate pharmacokinetics, pharmacodynamics and safety/ efficacy of a nonbiological complex drug's follow-on products in relevant patient populations [38,99,102,103]. As long as proof of therapeutic equivalence and similar safety profiles by appropriate studies is missing, interchange and automatic substitution between nonbiological complex drugs and their follow-on products should be discouraged [39].…”
Section: Regulatory Affairs and Experience With Is Follow-on Compoundsmentioning
confidence: 99%